Assessment of agro-based homestay activities towards Muslim friendly tourism - Othman, Rashidi; Azman, Adib; Hashim, Khairusy Syakirin Has-Yun; Radin, Hidayah; Adzhar, Mashhuda; Mahamod, Lukman Hakim; Ahmad Fadzillah, Nurrulhidayah (Human Resource Management Academic Research Society, 2019)
The homestay programme in Malaysia was first introduced in 1988 by the Ministry of Tourism as to match the demand of an emerging tourist segment and the alternatives for tourist of those who travel in the quest for the experience that enhances knowledge. Homestay can be defined as one type of lodging that the tourists share with the homeowner with the intention to learn culture and lifestyles from the homeowner. Malaysia is one of the Muslim countries in Southeast Asia that received billions of tourists all over the world. However, the provision of Muslim-friendly tourism accommodation is still lacking. Hence, the aim of this research to explore the interrelationship of agro-cultural based homestay activities, spatial organization, social interaction and landscape setting towards Islamic Built Environment. All these components need to be suitable for guests and hosts to reach the guideline abided by Islamic principles. Methods of observation throughout the house and interview conducted with the hosts are used to investigate the criteria of Shari’ah compliance applied. Based on the data analysis, the Shari'ah compliance abided by the guests and the hosts can sustain the cultural and the agro-tourism homestay that becomes their identity integrated with Islamic Built Environment from faded away. In conclusion, based on the findings of this study, the Shari'ah compliances implemented can enhance the quality of the activities, spatial organization, social interaction and the landscape setting in the homestay programme in the future.